2016
DOI: 10.1159/000477094
|View full text |Cite
|
Sign up to set email alerts
|

Use of Light Therapy by Office-Based Physicians

Abstract: Background: Light therapy (LT) is a non-pharmacological biological treatment that has been used in psychiatry since the 1980s. Previous research has investigated the usage of LT in hospitals. The aim of this study was to examine the pattern of use of LT by office-based physicians. Methods: A questionnaire was sent by mail to 400 randomly selected doctors in Austria. We made sure that the sample was equally representative of general practitioners (GPs) and psychiatrists, public health service doctors and privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Nonetheless, Farah et al [ 33 ] claimed that several non-pharmacological interventions are characterized by similar effectiveness, hence non-pharmacological therapies of patients in Poznan could be considered as sufficient and equally effective as those in Kiel. On the other hand, especially LT seems to be quite easy and cheap to incorporate and, according to the study conducted by Winkler-Pjerk et al [ 34 ], this method is not only frequently used in Germany, Austria and Switzerland, but is known as an effective intervention too.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, Farah et al [ 33 ] claimed that several non-pharmacological interventions are characterized by similar effectiveness, hence non-pharmacological therapies of patients in Poznan could be considered as sufficient and equally effective as those in Kiel. On the other hand, especially LT seems to be quite easy and cheap to incorporate and, according to the study conducted by Winkler-Pjerk et al [ 34 ], this method is not only frequently used in Germany, Austria and Switzerland, but is known as an effective intervention too.…”
Section: Discussionmentioning
confidence: 99%
“…They obtained 13.5% of affirmative answers for PMDD. 95 A research study also tested the efficacy of massage therapy in 24 women randomly assigned to a massage group or relaxation control group. The authors observed in massage group women a reduction in affective PMDD symptoms immediately after the first and the last massage sessions, thus suggesting that massage treatment could be considered as an adjunct therapy for treating severe premenstrual symptoms.…”
Section: Psychotherapy and Alternative Treatmentsmentioning
confidence: 99%